Connectedness with God: Reawakening Consciousness in Con-temporary Christianity and Religiosity in the light of Schleierma-cher’s Speeches - Tedjoworo, Hadrianus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2011)
Reading Schleiermacher’s Speeches might give rise to different experience of religion. It appears that the more important issue today is not the identity (being), but the communality and sociality, for communality is a ‘space’ where one’s being is able to move in its ‘becoming’. The importance of experience is now considered much more than before. In this article the emphasis on one’s experience and its connectedness with that of others is refreshed and further elaborated. Schleiermacher’s ideas question the traditional patterns of (Christian) communities, which to some extent have implanted uniformity, dogmatism and oppressions, as being responsible for the emergence of indifferentism today. Community, as Schleiermacher has pleaded in the Speeches, must be fluid and broadly inclusive. The immediate self-consciousness is depicted in the moment of ‘listening’—the world might have been blinded by appearances and made deaf by the voices, but there remains the process of listening. Maybe a time for a ‘listening’ religion? A ‘listening’ religious community? Keywords :*religion *fragmentation *virtuality *indifferentism *power*rational Christianity *institutional representation *fascination*'true' religion *appearances to experiences *intuition *feeling*continuous reciprocity *fluid and inclusive community